The Effect of Station-Based Learning with Descriptive Texts on the Topic of Daily Life on the Learning Interest of the Students in 11th Grade at SMAN 9 Malang - Muhammad Ihsan Aura Jiwa (Universitas Negeri Malang, 2021)
The purpose of this research is to find out whether the station-based learning (Stationenlernen) with descriptive texts on the topic of daily life (Alltagsleben) affects the learning interest of the students in 11th grade at SMAN 9 Malang. This research can be categorized as quantitative research using the ex-post-facto approach. The subjects were 32 students in 11th grade at SMAN 9 Malang. The data sources were descriptive texts on the topic of daily life (Alltagsleben) and also questionnaire results that are collected through the main instruments pretest, posttest, and questionnaire. Based on the research results, it is found that station-based learning (Stationenlernen) has a positive effect. The average score in the pretest was 75,6 and after implementing the station-based learning (Stationenlernen), the average score was higher at 89,6. Furthermore, the questionnaire results showed that 17 students had big learning interests and 15 others had medium learning interests.